(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2023)
This research aims to: 1) Provide essential meaning to create English teaching learning which is appropriate with the curriculum (lesson plan); 2) Learning new vocabulary in the classroom; 3) Establishing relationship with students or asserting authority of the lecture. This research is intended to analyze the type of code switching by using code switching in their class. This research used qualitative method.the sample in this study was student and lecturer in an English Learning. Data collections are observation, interview and documentation. The researcher listen to comprehensively the recording of the lecturer delivering his or her lecturing to analyze the data. In the observation, the researcher found that teacher stimulated students to mention some expressions of invitation. But, other students answered the question noisily. It made the teacher could not hear the answer clearly. Then, the teacher admonished them loudly. From the result above the researcher knows that code- switching according to the function used in teaching English is a technique to solve classroom problems